Network centrality analysis to determine the tactical leader of a sports team - Sasaki, K.; Yamamoto, T.; Miyao, M.; Katsuta, T.; Kono, I. (International Journal of Performance Analysis in Sport, 2017)
Purpose: The goal of this study was to clarify the defensive structures that play a decisive role in the game of Rugby football, which is a competitive team sport. Method: The study used data from games played under the Rugby Union code, and particularly on turnovers made during defensive plays in the 2015 Rugby World Cup. Social network centrality analysis was applied to analyse organisational strategies. A correspondence analysis performed using centering resonance techniques was shown to deepen our understanding of relationship structures in network mapping, while the application of network analysis was able to improve the description of complex passages of play. Result: Eigenvector centrality would reflect the specific network structures of one`s neighbour vertexes. It also reflects the centrality of all other vertexes that can be further reached from directly involved ones. Team sports rely on cooperation between teammates. The applications of network analysis would be one viewpoint of representing a society in which decision-making behaviours are taken on the basis of human relationships.